The Future of Bankruptcy Law: Problems and Orientation of Bankruptcy Regulation from A Responsive Law Perspective - Lira, M Adnan (Faculty of Law, Universitas Pekalongan, 2024)
The Indonesian Bankruptcy Law needs revision to address existing weaknesses, such as imbalances in legal protection and inability to accommodate digital economic developments, in order to become more responsive and adaptive to new challenges in the business world and global economy. This research aims to analyze the problems in applying the current Bankruptcy Law from a responsive law perspective and formulate future bankruptcy regulation orientations in accordance with responsive law principles. The study uses normative legal research methods with a conceptual approach, examining primary, secondary, and tertiary legal materials through literature review. Data analysis is conducted qualitatively with a descriptive-analytical approach, using deductive and inductive reasoning. Research results show that the current Bankruptcy Law application has several problems from a responsive law perspective, including imbalances in legal protection, lack of flexibility in debt restructuring, inability to accommodate technological and digital economic developments, and limitations in handling cross-border bankruptcies. To address these issues, future bankruptcy regulation orientations should include aspects such as creating balanced legal protection, emphasizing business rescue efforts, accommodating technological developments, handling cross-border bankruptcy complexities, providing better protection for workers and SMEs, and strengthening the role and capacity of relevant institutions, with the aim of creating a more fair, efficient, and responsive bankruptcy legal system to societal needs and new challenges in the business world.